Towards Test Coverage Criteria for Visual Contracts - Heckel, Reiko; Khan, Tamim; Machado, Rodrigo (Electronic Communications of the EASST, 2011)
When testing component-based or service-oriented applications we cannot always rely on coverage criteria based on source code. Instead, we have to express our requirements for testing at the interface level. Specifying interfaces by graph transformation rules, so-called visual contracts, we define model-based coverage criteria exploiting the well-known relations of causal dependency and conflict on transformation rules. To this end we establish an observational semantics for graph transformation systems with rule signatures formalising a notion of test execution, and define dependency graphs to provide a structure on which coverage can be analysed.